Polymorphic variants in the DLX1 gene and the risk of non-syndromic cleft lip with or without cleft palate - Gaczkowska, Agnieszka; Hozyasz, Kamil K.; Wójcicki, Piotr; Biedziak, Barbara; Jagodziński, Paweł P.; Mostowska, Adrianna (Journal of Medical Science, 2016)
Background. Non-syndromic cleft lip with or without cleft palate (NSCL/P) is a common developmental anomaly, which etiology is complex and not completely elucidated.Aim. The aim of the present study was to evaluate whether common polymorphisms in the distal-less homeobox gene 1 (DLX1) may contribute to the risk of orofacial clefts in the Polish population.Material and methods. Five single nucleotide variants were genotyped using high-resolution melting curve analysis in a group of 278 patients with NSCL/P and properly matched controls (n = 574).Results. Statistical analysis revealed that two variants located in the 3’ untranslated region of DLX1, rs788172 and rs788173, were associated with a decreased risk of NSCL/P (ptrend = 0.041 and ptrend = 0.025, respectively). The allelic frequencies for these polymorphisms were significantly lower in patients compared to healthy individuals (p = 0.040 and p = 0.024, respectively). However, all these results did not remain statistically significant after applying the Bonferroni correction for multiple comparisons. The results of single-marker analysis for DLX1 were confirmed by haplotype analysis. The best evidence of the haplotype association with the risk of NSCL/P was observed for the T-G-G haplotype consisting of rs1047889, rs788172 and rs788173 major alleles. This high risk haplotype was more frequent among cases than controls (p = 0.013, pcorrected = 0.026).Conclusions. We found evidence for the association between DLX1 gene variants and the risk of NSCL/P in the Polish population. To confirm our preliminary findings further, larger sample size studies are required.